PERMAINAN SIPAK RAGO DI MINANGKABAU DALAM KARYA SERIGRAFI - ARIGA SEPTIAN, Drs. Irwan, M.Sn, Yofita Sandra, S.Pd., M.Pd (Universitas Negeri Padang, 2015)
Older generation Minangkabau remember the various pamenan (game)I've ever played. There are some traditional games such Minangkabau; SipakRago, Ulu Ambek, Alang-alang (Darek and Pasisia), Randai (Silek), Buru Babi, and there are many traditional games scattered in West Sumatra. Game scattered in various places in Minangkabau. Perhaps hundreds, have the same role of play but different naming, play from one place to another.Traditional games were loaded philosophy of life, a variety of messagesand teachings of manners, morals and behavior. Through this game one can realize that he was not living alone in the community, and if there is a problem should be discussed in advance. By the very nature of traditional games played in groups, it can form the characters themselves are spirited leadership, togetherness, and high social spirit.Creation aims to visualize how Sipak Rago today are marginalized bymodernisation, in addition to the creation aims back to remember about the meaning contained in Sipak Rago very useful for anyone.Furthermore, techniques or methods used in making this thesis isserigraphy technique, which is a technique that is produced from silk stretch open to the plane of the mold is then filtered by using Squez made of rubber material as a tool for transferring ink from the screen to the print range. In the activity and the process of making the work is done, gave birth to the work of different, but each piece has a relationship with one another which are held together because they have a theme, an idea, a similar concep.After conducting a series of lengthy process of creating it creates tengraphic art with serigraphy techniques on paper are: 1) Urang-urang Sawah, 2) Rago Usang, 3) Ditepi Kehancuran, 4) Tergantingan, 5) Trophy, 6) Dirantai, 7) The End, 8) Basamo, 9) Perjuangan, 10) Digemari. Through the works of graphic art themed Sipak Rago, is expected to art students after seeing the work of authors can be uplifting in the work of art, can be used as a reference to create graphic art work better in the future.Kata Kunci: Tergantikan, Basamo, Dirantai